Cell death regulation in myocardial toxicity induced by antineoplastic drugs - Yu, Xue; Yang, Yan; Chen, Tianzuo; Wang, Yuqin; Guo, Tianwei; Liu, Yujun; Li, Hong; Yang, Liming (Frontiers in Cell and Developmental Biology, 2023)
In recent years, significant progress has been made in the development of new cancer therapies that have greatly improved patient survival, but may also lead to serious cardiac adverse effects. The mechanisms by which antineoplastic drugs cause cardiomyocyte death remain unknown. This article presents recent advances in antineoplastic drug-induced regulatory cardiomyocyte death pathways, including autophagy, ferroptosis, apoptosis, pyroptosis, and necroptosis. Mitochondria are key organelles for maintaining homeostasis in myocardial tissue, and this article focuses on the importance of mitochondrial homeostasis in cardiotoxicity.